Use of Punctuation in Journalistic Style - Klučková, Růžena (Univerzita Pardubice, 2013)
The work deals with the use of punctuation in journalistic style. It describes the use of punctuation in general, the use of selected types of punctuation marks and their functions. It focuses on the use of punctuation in a selected British broadsheet newspaper. By contrasting the standard usage with the use in journalistic style, it depicts the main differencies.
Použití interpunkce v žurnalistickém stylu
Keywords: punctuation; punctuation marks; commas; journalism; newspapers; interpunkce; interpunkční znaménka; čárky; žurnalistika; noviny